Formal Synthesis of (+)‐Laurencin by Gold(I)‐Catalyzed Intramolecular Dehydrative Alkoxylation. Issue 30 (3rd May 2017) - Lanier, Megan L.; Park, Hyeri; Mukherjee, Paramita; Timmerman, Jacob C.; Ribeiro, Anthony A.; Widenhoefer, Ross A.; Hong, Jiyong
Abstract: 8‐Membered cyclic ethers are found in a wide range of natural products; however, they are challenging synthetic targets due to enthalpic and entropic barriers. The gold(I)‐catalyzed intramolecular dehydrative alkoxylation of ω‐hydroxy allylic alcohols was explored to stereoselectively construct α, α′‐ cis ‐oxocenes and further applied in a formal synthesis of (+)‐laurencin. The gold(I)‐catalyzed intramolecular dehydrative alkoxylation may constitute an alternative method for the synthesis of molecular building blocks and natural products that contain highly functionalized 8‐membered cyclic ethers. Abstract : Go for gold ! 8‐Membered cyclic ethers are challenging synthetic targets found in a wide range of natural products. The gold(I)‐catalyzed intramolecular dehydrative alkoxylation of ω‐hydroxy allylic alcohols was explored to stereoselectively construct α, α′‐ cis ‐oxocenes and further applied in a formal synthesis of (+)‐laurencin. The gold(I)‐catalyzed intramolecular dehydrative alkoxylation may constitute an alternative method for the synthesis of highly functionalized medium‐sized cyclic ethers.